2020
DOI: 10.5860/crl.81.6.896
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Analysis of Faculty Opinions on and Perceptions of Research Impact Metrics

Abstract: We present a qualitative analysis of the results of a survey of faculty and researchers at a large Midwestern R1 university around their understanding of and attitudes toward scholarly metrics. The survey included opportunities for participants to provide freetext responses regarding their use of metrics and concerns they have about the use of metrics for assessment. Participants indicated they understand metrics and use them in a variety of ways, but they have concerns about administrators' potentially inappr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
(7 reference statements)
3
5
0
Order By: Relevance
“…As potential reasons for altmetrics' low popularity, Aung et al (2019) mention academics' insecurities regarding altmetrics' added value, missing encouragement of altmetrics‐ and social media usage from institutions, and privacy concerns, among others. The reoccurring finding of a comparatively low familiarity with altmetrics is in line with multiple other surveys across academic librarians (Miles, Konkiel, & Sutton, 2018) and faculty (Bakker et al, 2019; DeSanto & Nichols, 2017).…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…As potential reasons for altmetrics' low popularity, Aung et al (2019) mention academics' insecurities regarding altmetrics' added value, missing encouragement of altmetrics‐ and social media usage from institutions, and privacy concerns, among others. The reoccurring finding of a comparatively low familiarity with altmetrics is in line with multiple other surveys across academic librarians (Miles, Konkiel, & Sutton, 2018) and faculty (Bakker et al, 2019; DeSanto & Nichols, 2017).…”
Section: Introductionsupporting
confidence: 85%
“…In their follow‐up study, Ma and Ladisch (2019) revealed a discrepancy between interviewed researchers' attitudes toward metrics in practice and in principle: while in principle, most researchers would not trust metrics as objective indicators for quality, in practice they do actively use them for personal or administrative purposes, thereby relying on them as supposedly objective measures. A similar discrepancy was found in a recent qualitative survey across faculty, instructors, and researchers at the University of Minnesota about their attitudes toward research metrics (Bakker, Cooper, Langham‐Putrow, & McBurney, 2020). The participants stated several use cases metrics would fulfill for them, for example, in information‐seeking activities, as a means of self‐assessment, or in the assessment of other individuals.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…When assessing scientific literature, researchers may use metrics such as the JIF as an indicator of journal quality or rigor [ 41 ]. Our investigation found that both the retracted publications and systematic reviews citing the publication after the retraction was issued were more likely to be in JIF Q1.…”
Section: Discussionmentioning
confidence: 99%
“…While the extant literature often discusses the “usefulness” of altmetrics, many proposed uses are merely hypothetical and rarely demonstrate how to practically apply altmetrics in academic settings. More so, despite the growing body of literature on altmetrics, studies show that academics have little familiarity with altmetrics, and when they do, they typically do not find them valuable for promotion and tenure (P&T) 22,23 …”
Section: Introductionmentioning
confidence: 99%